Faktor-faktor yang Memengaruhi Milenial Berdonasi Online Melalui Crowdfunding Platform: Studi Pada Kitabisa.com - Nanda Amalia (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2020)
Abstract. Technological developments have made it easier for the community to collect donations online through crowdfunding platforms. According to Indonesian Millennial Report, millennials allocate their funds for social activities, such as donations, as much as 5.3 percent of their income. This study aimed to analyze factors that influence millennials to do onlinedonation through platform Kitabisa.com.This study selected a sample of 120 respondents of active muslim students of IPB University and TAZKIA Institute. This study used descriptive analysis and logistic regression method. The results of this study showed that the platform effectiveness and platform innovation are two main factors that influence millennials in donating online through the Kitabisa.com. Keywords: online donation, crowdfunding platform, millennial, logistic regression